Peningkatan Kemampuan Berbahasa Anak Usia 4-5 Tahun Menggunakan Media Video Animasi di Kelompok Bermain Sriwijaya Sadar Sriwijaya - Lestari, Yuyun (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The research aims to understand how educators use animation media to improve early childhood language skills and its impact during learning. The research method was carried out using classroom action research techniques at KOBER SRIWIJAYA in Bandar Sribhawono District. The research results showed that instructor training in utilizing animation media was not fully effective in Cycle I, so further action was needed in Cycle II. Cycle I got a score of 3.22 categorized as